Similar treatment outcomes for radical cystectomy and radical radiotherapy in invasive bladder cancer treated at a United Kingdom specialist treatment center. - Kotwal, S; Choudhury, A; Johnston, C; Paul, AB; Whelan, P; Kiltie, A (2008)
PURPOSE: To conduct a retrospective analysis within a large university teaching hospital, comparing outcomes between patients receiving either radical surgery or radiotherapy as curative treatment for bladder cancer. PATIENTS AND METHODS: Between March 1996 and December 2000, 169 patients were treated radically for muscle-invasive bladder cancer. Data were collected from patient notes. Statistical analyses were performed using Kaplan-Meier methods and Cox proportional hazards regression analysis to compare radiotherapy and surgical outcome data. RESULTS: There was no difference in overall, cause-specific, and distant recurrence-free survival at 5 years between the two groups, despite the radiotherapy group being older (median age, 75.3 years vs. 68.2 years). There were 31 local bladder recurrences in the radiotherapy group (24 solitary), but there was no significant difference in distant recurrence-free survival. In a more recent (2002-2006) cohort, the median age of radiotherapy patients but not the cystectomy patients was higher than in the 1996-2000 cohort (78.4 years vs. 75.3 years for radiotherapy and 67.9 years vs. 68.2 years for surgery). CONCLUSIONS: Although the patients undergoing radical cystectomy were significantly younger than the radiotherapy patients, treatment modality did not influence survival. Bladder cancer patients are an increasingly elderly group. Radical radiotherapy is a viable treatment option for these patients, with the advantage of organ preservation.